Small molecule angiotensin converting enzyme inhibitors: A medicinal chemistry perspective - Zheng, Wenyue; Tian, Erkang; Liu, Zhen; Zhou, Changhan; Yang, Pei; Tian, Keyue; Liao, Wen; Li, Juan; Ren, Changyu (Frontiers in Pharmacology, 2022)
Angiotensin-converting enzyme (ACE), a zinc metalloprotein, is a central component of the renin–angiotensin system (RAS), which controls blood pressure by regulating the volume of fluids in the body. ACE is also part of the kinin-kallikrein system, where it degrades bradykinin and other vasoactive peptides Notably, the classical RAS driven by ACE, as a key enzyme, has some deleterious effects, such as hypertension. Angiotensin-converting-enzyme inhibitors (ACE inhibitors, ACEis) are a class of medications used primarily for the treatment of high blood pressure and heart failure. ACEis decrease the formation of angiotensin II and increase the level of bradykinin, which relaxes blood vessels as well as reduces blood volume, lowers blood pressure and reduces oxygen consumption from the heart. In this review, we have summarized the research advances of ACE inhibitors, focusing on the development sources, design strategies and analysis of structure-activity relationships and the biological activities of ACE inhibitors.